Co-evolutionary dynamics of policy and system development : the case of marine renewable energy technologies - Fontes, Margarida (2019)
ABSTRACT: The transition to a sustainable energy system is a major societal challenge requiring profound trans-formations in existing socio-technical systems (Markard et al, 2012). These processes have been addressed by the sociotechnical transitions literature that called the attention to the role played by radically new technologies, being developed in niches, which have strong transformative potential (Kemp et al, 1998; Schot and Geels, 2007). These technologies and the socio-technical systems de-veloping around them often need temporary protection against the selection pressures of the estab-lished regimes (Smith and Raven, 2016); and supportive policies are a fundamental mode of protec-tion (Kivimaa and Kern, 2016). In the case of sustainable energy technologies, policy support is fur-ther justified by the need to accelerate the transition process (which is usually a long term process), given the urgency of fighting against climate change (IPCC, 2014).